Radiological dose assessment of natural radioactivity in Malaysian tiles using resrad-build computer code - Aznan Fazli Ismail,; Shittu Abdullahi,; Supian Samat,; Muhamad Samudi Yasir, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research reports the annual effective dose of dwellers based on the finding of natural radioactivity concentrations in Malaysian tiles. A total of 30 tiles samples obtained from the manufacturer or bought directly from local hardware store. Natural radioactivity was analyzed using gamma spectrometry system for 12 h counting times. The activity concentration of 226Ra, 232Th, and 40K in the analyzed samples ranged from 37.50 – 158.05 Bq kg-1, 42.22 – 80.19 Bq kg-1 and 349.46 – 750.18 Bq kg-1, respectively. The determined radium equivalent activity was below than the recommended limit of 370 Bq kg-1. The external dose received by dwellers due to natural radionuclides in tiles were projected for 1, 5, 10, 20 and 50 years through six exposure pathways using Resrad-build computer code. The results showed that the annual effective dose received by dwellers increased for the investigated timelines but still lower than the annual recommended limit of 1500 μSv. The simulation result also indicates that radon gas was the primary radiation exposure which contributes 80-94 % from the total radiation exposure to dwellers.